The possibilities of prosthetic rehabilitation of shortened dental arches in elderly patients - Tihaček-Šojić Ljiljana; Stančić Ivica; Jelenković Aleksandra; Milić-Lemić Aleksandra (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction. Functional consequences of posterior tooth loss are multiple; late and inadequate rehabilitation lead to further collapse of stomatognathic system, which is especially distinct in elderly population. Aim of this paper is to present advantages and disadvantages of different modalities of prosthetic treatment of shortened dental arch in elderly patients. Treatment with overdentures are convenient in this population because it is non-invasive and reversible. Periodontal problems and root caries are main complications of this treatment, but denture relaying after extraction and easy conversion into complete dentures facilitate resolving this complications. Removable partial dentures are one of the mostly indicated treatments for shortened dental arch. They improve masticatory efficiency, but disadvantages are in inferior aesthetic characteristics and comfort. Mechanical failures can be avoid by detailed analyze and correct planning. Treatment of shortened dental arch with fixed partial denture with distal extension can be very convenient solution for elderly patient. Osseointegration process and implant treatment promises every day more in prosthetic rehabilitation of elderly. Relayed prosthetic rehabilitation is recommended, not because of longer process of ossteointegration, but because of delayed recovery of soft tissues and general health condition of elderly. Conclusion. Each of before mentioned therapy modalities have its advantages and disadvantages in meaning of technical procedure, duration in function, possible complications and patient's comfort and satisfaction. In elderly patients, possible complications are more complex; therefore treatment must be done quickly, efficiently, and having in mind patient's general and oral health condition, level of cooperation and economic status.